2022
DOI: 10.1021/acs.jpclett.2c01361
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Free Energy of Small Water Clusters: Revisiting Classical Nucleation Theory

Abstract: By addressing the defects in classical nucleation theory (CNT), we develop an approach for extracting the free energy of small water clusters from nucleation rate experiments without any assumptions about the form of the cluster free energy. For temperatures higher than ∼250 K, the extracted free energies from experimental data points indicate that their ratio to the free energies predicted by CNT exhibits nonmonotonic behavior as the cluster size changes. We show that this ratio increases from almost zero for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…3,4 The precise way that gaseous vapor comes together to form prenucleation complexes, which eventually build to aerosols, and thus form CCN, is a very active area of research. 3,5–74 Much of this activity is driven by the uncertainty in how much aerosols and clouds will impact global warming. 75,76 While it is thought that in general more aerosols will lead to a cooling effect, the uncertainty in our knowledge exceeds the actual size of the predicted cooling.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The precise way that gaseous vapor comes together to form prenucleation complexes, which eventually build to aerosols, and thus form CCN, is a very active area of research. 3,5–74 Much of this activity is driven by the uncertainty in how much aerosols and clouds will impact global warming. 75,76 While it is thought that in general more aerosols will lead to a cooling effect, the uncertainty in our knowledge exceeds the actual size of the predicted cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Scaling and the quasiharmonic approach costs nothing in terms of computing time and we recommend their use. There is a broad range of computational evidence that reveals that while scaling is helpful, its impact is less than might be expected because we are commonly concerned with computing changes in the Gibbs free energies, ∆ G Ꝋ , and scaled versus unscaled ∆ G Ꝋ values tend to be within 1 kcal/mol for clusters up to five molecules 82–85,92,136,140,141,144–152 . While scaling systematically reduces the DLPNO‐CCSD(T)/CBS ∆ G Ꝋ values relative to the unscaled RRHO approach for hydration of glycine by fractions of a kcal/mol, the quasi‐harmonic approach increases the ∆ G Ꝋ values by several kcal/mol for a glycine hydrated with three or four waters 84 …”
Section: Cluster Configurational Sampling and Quantum Chemistry Methodsmentioning
confidence: 99%
“…5,6 Many studies have demonstrated the driving effect of sulfuric acid (SA) in forming prenucleation clusters, especially in the presence of other atmospheric acids and bases. 7–74 Hydrochloric acid (HCl), on the other hand, has not been as well studied for its potential role in the formation of pre-nucleation clusters. 75 It is estimated that 85% of the HCl in the atmosphere is produced from acid displacement of sea salt aerosols.…”
Section: Introductionmentioning
confidence: 99%